Determinants of Trust in Health Information Technology: An Empirical Investigation in the Context of an Online Clinic Appointment System. Issue 12 (20th July 2020) - Xie, Heng; Prybutok, Gayle; Peng, Xianghui; Prybutok, Victor
ABSTRACT: An online clinic appointment system (OCAS) is an example of health information technology (HIT) innovation in the healthcare industry. An OCAS can help healthcare organizations to improve the efficiency of information exchange for patients and transform a clinic-centered practice into patient-centered practice. This research uses an enhanced trust model to investigate the trust formation mechanism in the HIT context using OCAS as a proxy. We collected survey data from young adults to study the patients' perspectives and assess the proposed research model. The results support that five trusting base constructs have a statistically significant influence on the development of trusting beliefs in the use of OCAS, including situational normality, structural assurance, cognitive trusting base, perceived ease of use, and self-efficacy. We discuss theoretical contributions to trust formation in HIT and practical insights for healthcare organizations to utilize in developing and implementing patient focused HIT.